Genetic associations of conformation, finishing precocity and muscling visual scores with mature weight in Nelore cattle - Boligon, A. A. [UNESP]; Mercadante, M. E. Z.; Albuquerque, Lucia Galvão de [UNESP] (Elsevier B.V., 2011)
Were estimate (co)variance and genetic associations between conformation, finishing precocity and muscling visual scores measured at weaning (SCW, SFW and SMW, respectively) and yearling (SCY. SFY and SMY, respectively) with mature weight (MW) in Nelore cows, in order to predict the possible changes that inclusion of visual scores in beef cattle selection indices would bring to female mature weight. The data set contained records of 36,757 females, born between 1993 and 2006, belonging to the Jacarezinho cattle raising farm. (Co)variance components were estimated by bivariate animal models using Bayesian inference method through Gibbs sampling, assuming a linear model for MW and a nonlinear (threshold) model for conformation, finishing precocity and muscling visual scores. The first 10,000 rounds were considered as the burn-in period and discarded. The posterior means of direct heritability distributions were: 0.16 +/- 0.02 (SCW); 0.20 +/- 0.02 (SFW); 0.19 +/- 0.02 (SMW); 0.24 +/- 0.02 (SCY); 0.31 +/- 0.02 (SFY); 0.32 +/- 0.02 (SMY) and 0.46 +/- 0.04 (MW). Estimates of genetic correlations between visual scores and MW were positive and moderate, ranging from 0.27 +/- 0.06 to 0.36 +/- 0.04. Visual scores and MW should respond favorably to direct selection. Mature weight can be used in Nelore breeding programs designed to monitor the cows' size. Selection of animals with higher conformation, finishing precocity and muscling scores, especially at yearling, should promote an increase in cows' mature weight. (c) 2010 Elsevier B.V. All rights reserved.
Keywords: Bayesian inference; Beef cattle; Gibbs sampling; Productive traits